Spatiotemporal variability of lightning activity over the railway network in Sri Lanka with special attention to the proposed suburban railway electrification network - Maduranga, U. G. D.; Edirisinghe, M.; Alahacoon, Niranga; Ranagalage, M. (MDPI, 2022)
This study is oriented towards the investigation of the spatiotemporal variability of the lightning activity over the railway network in Sri Lanka using -lightning data from 1998 to 2014 that were downloaded from the database of Lightning Imaging Sensor (LIS) onboard NASA’s Tropical Rainfall Measuring Mission (TRMM). The study has also been extended to study the lightning activity over the proposed suburban railway electrification network. GIS was used to conduct an annual and seasonal analysis of the railway network, which consists of nine major railway lines, to identify vulnerable stations and segments. The average annual lightning flash density over a 1447 km-long railway network of Sri Lanka varies between 5.08–16.58 flashes/(km2 year). The railway lines run across the western and southern regions of the country have been identified as being in areas with higher lightning activity. In comparison to other railway lines, the Kelani Valley line in the Colombo district and Colombo-Maradana to Polgahawela segment of the Mainline are particularly vulnerable to lightning activity. These areas have also been recognized as regions with higher population density. The proposed 102 km long railway electrification network in Sri Lanka is also within higher population density segments, with higher lightning flash density values between 10.55–16.53 flashes/(km2 ·year). As a result, to improve the operational efficiency of the proposed electrification network, a fully coordinated lightning protection system in accordance with the findings of this study is strongly suggested.